The black female body: Representation of the erotic in contemporary visual art in Africa - Tayler FRIAR (E-REA)
Black sexual politics and its interaction with the eroticized female body in African art are still surprisingly underexplored topics in African academia (“African” not “Africanist”, to follow the distinction made by Jones in “African Scholarship, Eurocentricism and the Politics of Knowledge”). This gap is curious given the surge of contemporary African artists utilizing erotic imagery generated through 18th-century scientific racism, and its perpetuation in the imperialist epistemic structures of institutions — such as museums — in the centuries following. An icon such as Sara Baartman, the South African Khoikhoi woman exhibited at European freak shows in the early 1800s, is a poignant example of haunting images that represent the spectacular denigration of the black female body. Moreover, historically, the artistic canon has often given the perception of the black woman’s body as grotesque, animalistic, systematically subordinate, or fetishized. However, through artwork, the same body that was once unsightly has become a call to arms, suggesting that instead of continued victimization, black women wield the ‘erotic’ body as a resistance tool. African female artists are engaging with themes of eroticism and sexuality as inextricably entangled with historical violence and trauma through performance, live art, and painting. This article aims to interrogate the use of the erotic as a mechanism to navigate the complex terrain of post-colonial identities, power, and the abiding historical ‘weight’ of the colonial archive. To accomplish this, it will present several fundamental arguments that feed into black feminist interrogations of the body including a meditation on body politics and gender being rewritten into the colonial paradigm. Through the examination of the work of two prominent artists — Tracey Rose and Lady Skollie of South Africa — the author synthesizes various representations of the erotic, coupled with how it engages with issues of history and reappropriation of the black female form. Using Baartman as a guiding symbol, this article will argue that contrary to its previous confinements as an overly policed trope, the black female body is charged with an artistic power that explodes, leaks, and subverts the historical narrative, making it a constantly evolving archetype in contemporary visual art.